The role of B2M in cancer immunotherapy resistance: function, resistance mechanism, and reversal strategies - Han, Xiaowen; Zhang, Jiayi; Li, Weidong; Huang, Xiaodong; Wang, Xueyan; Wang, Bofang; Gao, Lei; Chen, Hao (Frontiers in Immunology, 2025)
Immunotherapy has emerged as a preeminent force in the domain of cancer therapeutics and achieved remarkable breakthroughs. Nevertheless, the high resistance has become the most substantial impediment restricting its clinical efficacy. Beta-2 microglobulin (B2M), the light chain of major histocompatibility complex (MHC) class I, plays an indispensable part by presenting tumor antigens to cytotoxic T lymphocytes (CTLs) for exerting anti-tumor effects. Accumulating evidence indicates that B2M mutation/defect is one of the key mechanisms underlying tumor immunotherapy resistance. Therefore, elucidating the role played by B2M and devising effective strategies to battle against resistance are pressing issues. This review will systematically expound upon them, aiming to provide insight into the potential of B2M as a promising target in anticancer immune response.